Electronic Support Effects of Tunable Mixed Metal Oxides on Immobilized Palladium N‐Heterocyclic Carbene Complexes. Issue 20 (24th May 2018) - Finn, Matthew T.; Donahue, Courtney M.; Blake, Anastasia V.; An, Nan; Daly, Scott R.; Voutchkova‐Kostal, Adelina M.
Abstract : Electronic effects of supports on site‐isolated organometallic complexes are poorly understood, despite indication that such effects impact stability and reactivity of immobilized complexes. Here we report X‐ray photoelectron spectroscopy (XPS) and X‐ray absorption near edge structure (XANES) spectroscopy studies of surface‐immobilized Pd II N‐heterocyclic carbene complexes on Mg‐Al mixed metal oxides (MMOs) using silane‐modified ligands. XPS revealed a ca. 1 eV increase in Pd binding energy as a result of immobilization on MMOs, suggesting that the Pd II complex becomes more electropositive when appended to the surface. For MMOs doped with Fe, Ni, Co and Zn, analysis of Cl K‐edge and Pd L2 ‐ and L3 ‐edge showed increasing pre‐edge energies that followed the order Fe = Ni < Zn = Cr < undoped Mg‐Al MMO. The Pd L3 pre‐edge energies correlated to the calculated oxygen partial charge of the MMO, as estimated using the Sanderson electronegativity model. Transmission electron microscope images collected on the immobilized Pd complexes revealed nanoparticles on three of the five MMOs, whose presence can be related to the Pd XPS and XANES energies. These findings suggest that electronic differences associated with the MMO supports impact the stability of appended Pd II complexes with respect to reduction to Pd 0 . Abstract : Here we report XPS and XANES spectroscopy studies of surface‐immobilized Pd II N‐heterocyclic carbene complexes on Mg‐Al mixed metal oxides (MMOs) using silane‐modified ligands.